Penerapan Sistem Informasi (Komputerisasi Kegiatan Pertanahan) dalam Mencapai Good Governance pada Kementerian Agraria dan Tata Ruang/ Badan Pertanahan Kota Magelang - Wira Pradipta; Utpala Rani (Journal of Economics and Business Aseanomics (JEBA), 2020)
Management of data and information in an institution can support national development, but some are still less effective and efficient. This study aims to determine the application of information systems to achieve Good Governance in the Ministry of Agrarian Affairs and Spatial Planning / Land Agency of Magelang City. The method used in this study was interviews with staff at the Magelang City Land Agency. The results find that the development of information technology and supporting infrastructure created opportunities to develop a more reliable, efficient, and timely computerized application for land activities (KKP) within the National Land Agency (BPN). The growing need for more accessible land information demanded by the community (policy recipients) and the government (policymakers) has increased higher than before. However, on the other hand, there are obstacles, such as the unfinished mapping of land parcels. The implication of this research is the Land Office needs to guide operators to better service quality.